Sentiment Based Product Recommendation System for E Commerce Using Machine Learning Approaches (International Journal of Innovative Research in Computer Science & Technology, 2022)
Today, e-commerce is a thriving industry.  We do not need to approach every customer to accept their  orders here. A business creates a website to offer things to  clients, who can then purchase the stuff they need within  the same website. These e-commerce firms include well known ones like Amazon, Shopify, Myntra, Flipkart, and  Ajio. To create a product recommendation system for the  end customers, we will be using the data set of e-commerce  product reviews in this final project. A sentiment analysis  model will be used to enhance the suggestions. Under this  final project, we will develop a sentiment analysis engine  utilising a variety of machine learning approaches before  selecting the model that produces the best results.
Keywords: Recommender Systems; Logistic Regression and Analysis; Random Forest; Xgboost; Hyperparameter Tuning; Deployment